Volumetric and viscosity properties of glycine in ionic liquid + water solutions at 298.15 K. (January 2019) - Zhao, Yajing; Chen, Yujuan; Fang, Mengyao; Zhang, Honghao; Zhuo, Kelei
Graphical abstract: Highlights: Densities and viscosities of glycine in aqueous solutions of ILs ([C2 mim]Br, [C4 mim]Br, [C6 mim]Br) were measured. Values of V Φ 0 and Δ t V Φ 0 increase with increasing IL concentrations and follow the order: [C2 mim]Br > [C4 mim]Br > [C6 mim]Br. The B -coefficients at given molalities of the ILs are in the order: [C2 mim]Br < [C6 mim]Br < [C4 mim]Br. These phenomena were explained by means of the structural hydration interaction model. Abstract: Densities and viscosities for the glycine + 1-alkyl-3-methylimidazolium bromide ([C n mim]Br, n  = 2, 4, 6) ionic liquids (ILs) + water systems were measured at 298.15 K. Meanwhile, the apparent molar volumes, V Φ, infinite dilution apparent molar volumes, V Φ 0, standard volumes of transfer, Δ t V Φ 0, of glycine and volumetric interaction parameters were further calculated. The viscosity B -coefficients of glycine in the aqueous IL solutions were calculated by using the Jones-Dole equation. The results show that both V Φ 0 and Δ t V Φ 0 values for glycine are positive and increase with increasing IL concentrations and follow the order: [C2 mim]Br > [C4 mim]Br > [C6 mim]Br. However, the B -coefficients at given molalities of the ILs are in the order: [C2 mim]Br < [C6 mim]Br < [C4 mim]Br. These phenomena are discussed and interpreted by means of the structural hydration interaction model and aggregation behavior of the [C6 mim]Br in water. This work provides the important basic data for the understanding of the interaction between the ILs and amino acids/proteins and for the design of industrial processes.